Cancer ‘survivor-care’: I. the α7 nAChR as potential target for chemotherapy-related cognitive impairment - Raffa, R. B. (2010)
WHAT IS KNOWN AND OBJECTIVE: Far more patients are now surviving cancer than ever before because of major advances in the diagnosis and treatment of primary and metastatic malignancy. Adjuvant chemotherapeutic drug and combination regimens have contributed to the success. However, persistent residual adverse effects involving mild impairment of cognitive impairment have been reported. Our objective is to review and to comment on the basic science and clinical evidence of potential pharmacologic targets for managing this emerging concern. COMMENT: A search was conducted of basic science and clinical literature related to the objective and the information obtained was organized and evaluated from the perspective of its insight into potential pharmacotherapeutic targets. A large body of evidence suggests that the nicotinic acetylcholine receptor (nAChR), and in particular the α7 subtype, is involved in memory and that agonists and positive allosteric modulators of this receptor have potential in schizophrenia and Alzheimer animal models and patients. WHAT IS NEW AND CONCLUSION: We identify significant indirect evidence that the selective α7 nAChR drugs that are currently being investigated for cognitive improvement in schizophrenia and Alzheimer disease patients may be useful in cancer chemotherapy-related cognitive impairment. The clinical use of those drugs should be explored.